The role of partners, parents and friends in shaping young women's reproductive choices in Peri-urban Nairobi: a qualitative study - Anja Zinke-Allmang; Amiya Bhatia; Krittika Gorur; Rahma Hassan; Amy Shipow; Concilia Ogolla; Kees Keizer; Beniamino Cislaghi (BMC, 2023)
Plain language summary Women's decisions to use family planning (FP) are influenced by social norms, the unwritten rules of appropriate actions within social networks, and are shaped by advice and information received from key influencers-important individuals who shape what is acceptable within social networks. The aim of this study was to understand how key influencers uphold and transmit information and norms about FP, and explore who women consult as they make FP decisions and why they consult these key influencers. We interviewed 16 women, 10 partners and 14 key influencers in peri-urban Nairobi, Kenya. We found that key influencers for decisions about FP included mothers, aunts, partners, friends and healthcare providers. In making a decision about FP use, women consulted key influencers based on who they deemed trustworthy to keep their FP use secret and described less trust to speak with men about FP in their social networks. Mothers understood the social risks of using FP and so could advise on its discreet use, and aunts were approachable sources of impartial information about FP. Although women identified partners as key decision makers, they were aware that power imbalances might affect final FP choices. Our findings underscore the importance of FP interventions working with women's social networks and to address social norms influencing women's decisions in using FP. Interventions to change FP norms should consider dynamics of secrecy, trust and emotional closeness that affect FP discussions among women's networks.